Positive Urine Cultures: A Major Cause of Inappropriate Antimicrobial Use in Hospitals? - Samuel A Silver; Laura Baillie; Andrew E Simor (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Urine specimens are among the most common samples submitted for culture to microbiology laboratories. The objectives of the present study were to describe the indications for obtaining urine cultures in a cohort of hospitalized patients, and to determine the appropriateness of antimicrobial therapy in response to urine culture results.